Esports Gambling: Market Structure and Biases. Issue 1 (January 2021) - Sweeney, Kevin; Tuttle, M. H.; Berg, M. Douglas
Esports is one of the fastest growing avenues of entertainment in the world today, projected to have revenues approaching US1.5 billion by year 2020. The large growth of this market has led to similarly large growth in the gambling industry around esports, with some estimates predicting over US7.4 billion in wagers made in 2018. In this article, we explain the nuances of the esports gambling market that differentiate it from the traditional sports betting market, such as "skins" betting, and empirically examine the biases present in wagering for two different esport titles ( Counter-Strike: Global Offensive and Dota 2 ) at two esports gambling websites. We find that real money and skins gambling markets have different types of market biases. In particular, we find that bettors in real money markets tend to overbet large underdogs, particularly when those underdogs are European teams playing against non-European teams.